Manajemen Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di SMPN 5 Janapria - sarbini, sarbini (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The purpose of this study was to determine how the planning, implementation and supervision and evaluation of school principals in improving the quality of education at SMPN 5 Janapria, Central Lombok district. This type of research is descriptive qualitative by using interviews, observations, and documentation as data collection. Analyze data by compiling data, managing data, then describing it systematically. The result of the principal's management in improving the quality of education at SMPN 5 Janapria, Central Lombok Regency is that the principal holds a meeting to plan the annual program, then the results of the meeting will be disseminated to teachers, students, parents and school committees, so in improving the Quality of Education the activities of the principal such as: reading the Koran every morning, Tahfiz Qur'an, Nahu and English Clubs, then getting students to be close to the Qur'an by doing these activities every day on a regular basis. Then in the learning process, the principal recommends that teachers use varied methods, discipline in entering classes according to the schedule, having job responsibilities, deliberation in deciding problems, openness in terms of costing in accordance with the agreed RKAS.